Relationship between perceived fear of COVID-19 and self-care management in heart failure patients - Yeni, Tuğba; Bülbül, Elif; Efil, Sevda; Yıldız-Ayvaz, Meryem; Türen, Sevda; Hiçerimez, Ayfer (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The fear of contracting COVID-19, which affects human health biopsychosocially, is expected to affect the self-care management of patients with heart failure (HF). This study was conducted to investigate the relationship between perceived fear of COVID-19 and self-care management in HF patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study was conducted with 115 HF patients. “Sociodemographic characteristics form”, “Fear of COVID-19 tool” and “Nine-item European Heart Failure Self-care Behavior Scale (EHFScB Scale-9)” were used to collect data. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. 51.3% of the participants in the study are in the 40–60 age range, 53.7% are male, 92.2% live with their family, 64.3% have a diagnosis of HF for less than 5 years. Levels of COVID-19 fear, and self-care management were found to be high in the participants who are 40 years old or younger, has higher education level, diagnosed within 1 to 3 years, received psychological support during the pandemic process, received training from doctor or nurse about COVID-19. Fear level and self-care levels were moderately positively correlated. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. During the COVID-19 pandemic, it is necessary to develop effective care strategies to identify individuals with diseases such as HF who should have high self-care management skills.